Magnitude, structure and dynamics of chronic unemployment in Denmark, Finland and Germany - Aho, Simo; Konle-Seidl, Regina; Norup, Iben; Rhein, Thomas; Rothe, Thomas (Nürnberg, 2019)
"Individual unemployment spells are frequently interrupted by short casual employment, by participation in active labour market policy (ALMP) measures or by periods outside the labour force. Such episodes end unemployment spells but afterwards the person gets often unemployed again, and the conventional statistics do not capture the actual length of the individual problem of being without a 'real' job in the longer run. To better grasp this problem of repeated unemployment we analyse unemployment trajectories of individuals with weak links to the labor market in the longer run. For this purpose, we introduce the concept of 'chronic unemployment' (CU). Our empirical analysis applies unique comparable and very detailed longitudinal register data to study the CU problem in Denmark, Finland and Germany. We find that chronically unemployed make up about one third of all unemployed in all three countries. This means that a substantial part of the unemployed has not gained a stable foothold in the open labour market for a long time. Individual factors strongly influence the probability of being chronically unemployed. CU becomes more common with age and decreases as the level of education increases. Although persistence in CU is highest in Germany, the country realizes higher transition rates into stable employment than the Nordic countries. Active labour market policy measures have a positive impact on the transition from chronic unemployment to non-subsidized employment, particularly wage subsidies in the private sector and occupational training and qualification."